Efecto del Guano de las Islas en el rendimiento de lactuca sativa l. var. dark green boston en Santiago de Chuco, La Libertad - Rebaza Vásquez, Olga Delmira (2017)
The present investigation was carried out during the months of September 2016 to February 2017 in the Santa Monica neighborhood of Andamarca, located in the district and province of Santiago de Chuco. The objective of this study was to evaluate the effect of guano on the islands and determine the best fertilization dose to obtain the highest yield of Lactuca sativa L. var. Dark Green Boston. In order to determine its effect and the best dose for this crop, a completely randomized block statistical design (DBCA) with four treatments and three repetitions was used. The treatments used were T0 without application (control), T1 (1 t.ha-1), T2 (1.5 t.ha-1), T3 (2 t.ha-1), respectively. The analysis of variance and the Tukey test were used for the statistical evaluation, at 5% significance. The results showed that the height, diameter, and plant weight variables are affected by the application of the guano of islands in comparison with the control; the highest yield was obtained with the T3 treatment, achieving (34.4 t.ha-1) of commercial lettuce in addition to favoring the highest plant height (17.4cm) and weight (231.1g) of Lactuca sativa L. var. Dark Green Boston in Santiago de Chuco, La Libertad.